THE ROLE OF UNIONS IN ADDRESSING AI-INDUCED JOB DISPLACEMENT: A REVIEW STUDY - Zamri, Aliaa Diyana; Abd Halim, Siti Noorjannah; Wan Anis , Wan ‘Aliaa (INTERNATIONAL JOURNAL OF LAW, GOVERNMENT AND COMMUNICATION (IJLGC), 2025)
This study examines the pivotal role of labour unions in mitigating the challenges posed by artificial intelligence (AI) and automation on job security and employee retention. As AI technologies increasingly replace human labour across various sectors, unions emerge as essential advocates for workers' rights, ensuring their inclusion in the design and implementation of these technologies. The research focuses on the relationship between perceived union effectiveness (independent variable) and employee retention (dependent variable) in AI-induced job displacement. By analysing recent studies and current union strategies, this paper highlights how effective union representation can enhance job security and facilitate workforce adaptation to technological changes. Findings show that proactive reskilling programs led by unions can increase retention by up to 64%, while ethical AI governance improves transparency and worker trust. Recommendations include collaborative training programs, adoption of AI ethics policies, and international regulatory frameworks. This review contributes to academic theory on labor relations in the AI era and offers policy implications for industry and governments.